2010
DOI: 10.1002/jclp.20707
|View full text |Cite
|
Sign up to set email alerts
|

Honoring children, mending the circle: cultural adaptation of trauma‐focused cognitive‐behavioral therapy for American Indian and Alaska Native children

Abstract: American Indians and Alaska Natives are vulnerable populations with significant levels of trauma exposure. The Indian Country Child Trauma Center developed an American Indian and Alaska Native (AI/AN) adaptation of the evidence-based child trauma treatment, trauma-focused cognitive-behavioral therapy. Honoring Children, Mending the Circle (HC-MC) guides the therapeutic process through a blending of AI/AN traditional teachings with cognitive-behavioral methods. The authors introduced the HC-MC treatment and ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 8 publications
0
92
0
Order By: Relevance
“…TF-CBT (Cohen, Mannarino & Deblinger, 2006; www.musc.edu/tfcbt) has several randomized controlled trials supporting its efficacy in treating many outcomes, including child behavior problems, safety skills, social competence, depression, PTSD, traumatic grief, child shame, and parental reactions to child trauma (Cohen & Mannarino, 2004; Cohen, Berliner & Mannarino, 2010; Cohen, Deblinger, Mannarino & Steer, 2004; Cohen et al, 2006; King et al, 2000). Studies have also shown that TF-CBT is adaptable across different cultures (BigFoot & Schmidt, 2010; Huey & Polo, 2008). The literature on cross-cultural adaptation of TF-CBT (e.g., BigFoot & Schmidt, 2010), as well as the wider literature on EBT (Patel et al, 2011; Verdeli et al, 2003; Verdeli et al, 2008) suggest that modifications are primarily on methods of implementation (rather than core concepts), simplifying text, and reducing jargon.…”
Section: Background Feasibility Studymentioning
confidence: 99%
See 2 more Smart Citations
“…TF-CBT (Cohen, Mannarino & Deblinger, 2006; www.musc.edu/tfcbt) has several randomized controlled trials supporting its efficacy in treating many outcomes, including child behavior problems, safety skills, social competence, depression, PTSD, traumatic grief, child shame, and parental reactions to child trauma (Cohen & Mannarino, 2004; Cohen, Berliner & Mannarino, 2010; Cohen, Deblinger, Mannarino & Steer, 2004; Cohen et al, 2006; King et al, 2000). Studies have also shown that TF-CBT is adaptable across different cultures (BigFoot & Schmidt, 2010; Huey & Polo, 2008). The literature on cross-cultural adaptation of TF-CBT (e.g., BigFoot & Schmidt, 2010), as well as the wider literature on EBT (Patel et al, 2011; Verdeli et al, 2003; Verdeli et al, 2008) suggest that modifications are primarily on methods of implementation (rather than core concepts), simplifying text, and reducing jargon.…”
Section: Background Feasibility Studymentioning
confidence: 99%
“…Studies have also shown that TF-CBT is adaptable across different cultures (BigFoot & Schmidt, 2010; Huey & Polo, 2008). The literature on cross-cultural adaptation of TF-CBT (e.g., BigFoot & Schmidt, 2010), as well as the wider literature on EBT (Patel et al, 2011; Verdeli et al, 2003; Verdeli et al, 2008) suggest that modifications are primarily on methods of implementation (rather than core concepts), simplifying text, and reducing jargon. One component of TF-CBT that was hypothesized to require some adaptations in LMIC is parenting skills.…”
Section: Background Feasibility Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bigfoot and Schmidt report the integration of trauma-focused care with traditional American Indian practices. 80 …”
Section: Cultural Considerationsmentioning
confidence: 99%
“…However, small sample sizes of racial and ethnic populations in randomized, controlled trials research prevent strong and clear conclusions about the effectiveness, generalizability, and appropriateness of EBPs delivered to racial and ethnic minority communities. Prior research indicates the importance of addressing culture in mental health services and treatment, as culturally adapted treatments are more likely to yield positive results (BigFoot & Schmidt, 2010;Harris & Franklin, 2003;Muñoz & Mendelson, 2005;Sue, 2003).…”
mentioning
confidence: 99%